The Competence of Student’s Performance to Strengthen Faculty of Public Health, Nakhon Ratchasima Rajabhat University - สันติวงศ์, ชนาธิป (Ratchaphruek Journal, 2018)
The purpose of this research was to evaluate the competency of student’s work in Faculty of Public Health, Nakhon Ratchasima Rajabhat University (NRRU) in terms of 1) family health care, 2) satisfaction on the family health care service, 3) community health development, and 4) satisfaction on the community health development services. The samples consisted of 271 students who were studying in the fourth year (batch 4) of Bachelor degree of Public Health program (Community Public Health). The research instrument consisted of 4 sets of questionnaires to evaluate the work capability of the students in 4 parts to evaluate the competency of student’s work. Cronbach’s alpha coefficient was calculated for reliability of the questionnaires. The reliability of the 4 sets of questionnaires were 0.88, 0.84, 0.94, and 0.91, respectively. The research findings were as follows: students’ work capabilities were at the good level on the family healthcare ( = 4.25), community health development ( = 4.13), satisfaction of receivers on the family health care services were at the very high-level ( = 4.61) and the high-level ( = 4.41) on the community health development service. The results of the study suggested that the competency of students’ work of Bachelor degree of Public Health program (Community Public Health) met the requirement of Faculty of Public Health, NRRU.